Quality of intrapartum care at Mulago national referral hospital, Uganda: clients’ perspective - Kigenyi, Omar (BioMed Central, 2013)
BACKGROUND: Quality of intrapartum care is an important intervention towards increasing clients’ utilization of skilled attendance at birth and accelerating improvements in newborn’s and maternal survival and wellbeing. Ensuring quality of care is one of the key challenges facing maternal and neonatal services in Uganda. The study assessed quality of intrapartum care services in the general labor ward of the Mulago national referral and teaching hospital in Uganda from clients’ perspective. METHODS: A cross sectional study was conducted using face to face interviews at discharge with 384 systematically selected clients, who delivered in general labor ward at Mulago hospital during May, 2012. Data analysis was done using STATA Version (10) software. Means and median general index scores for quality of intrapartum care services were calculated. Linear regression models were used to determine factors associated with quality of care. RESULTS: Overall, quality of intrapartum care mean index score was 49.4 (standard deviation (sd) 15.46, and the median (interquartile range (IQR)) was 49.1 (37.5–58.9). Median index scores (IQR) per selected quality of care indicators were; dignity and respect 75 (50–87.5); relief of pain and suffering 71.4 (42.8-85.7); information 42.1 (31.6-55.3); privacy and confidentiality 33.3 (1–66.7); and involvement in decision making 16.7 (1–33.3). On average, higher educational level (college/university) (β: 6.81, 95% CI: 0.85-15.46) and rural residence of clients (β: 5.67, 95% CI: 0.95-10.3) were statistically associated with higher quality scores. CONCLUSION: This study has revealed that quality of intrapartum care services from clients’ perspective was low. Improvements should be focused on involving clients in decision making, provision of information about their conditions and care, and provision of privacy and confidentiality. There is also need to improve the number and availability of health care providers in the labor ward.